Philander opossum as prey of Didelphis marsupialis in a rainforest in México - Rojas-Sánchez, J. Vladimir; Sánchez-Cordero, Víctor; Coates, Rosamond; Hernández-Jauregui, Mauricio; Flores-Martínez, José Juan (Therya Notes, 2023)
Neotropical rainforests hold a high mammalian diversity with complex species interactions. Opossums are a common group of mammals inhabiting these forests. In México, the common opossum Didelphis marsupialis and the four-eyed opossum, Philander opossum are sympatric species in these forests. The study site is located at Los Tuxtlas Biological Station in Veracruz, México. We filmed a video in situ of an interaction between 2 species of opossums using a cell phone camera. The morphological characteristics of both species of opossums correspond to adult individuals of D. marsupialis and P. opossum. The video shows an individual of D. marsupialis crossing a trail and carrying a corpse of an individual of P. opossum in its snout. We document the first report of P. opossum as a prey of D. marsupialis in a rainforest in México and discuss whether it was due to predation or to an opportunistic encounter of a corpse that was removed for later consumption. Didelphis marsupialis is known to act as a scavenger and to hunt other opossum species. Our observations coincide with a study documenting a predation event of D. marsupialis over P. opossum in Barro Colorado, Panamá, and adds valuable information on D. marsupialis feeding habits in tropical rainforests.